2017
DOI: 10.4274/cayd.86548
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Children Admitted to the Emergency Department with Convulsive Epileptic Seizures: A Single-Center Study

Abstract: Introduction:To evaluate the etiology and characteristics of children admitted to the emergency department with an acute convulsive epileptic seizure. Methods: Data of patients who were admitted to the emergency department with a convulsive epileptic seizure were reviewed. The patients were divided into febrile seizure, first idiopathic non-febrile seizure, idiopathic epilepsy, symptomatic epilepsy, and symptomatic seizure groups. Results: A total of 335 children were included in the study. Febrile seizures we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
1
1
1
Order By: Relevance
“…3 In a prepandemic study by Berksoy et al, which included 335 patients who presented to the pediatric ED with convulsive seizures, 38.5% were febrile, 17.6% first afebrile, 35.8% idiopathic epilepsy, 8.1% symptomatic epileptic, and 1.5% symptomatic. 9 Our results were similar. The rate of febrile seizures was 33.6% and epilepsy 35.6%.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…3 In a prepandemic study by Berksoy et al, which included 335 patients who presented to the pediatric ED with convulsive seizures, 38.5% were febrile, 17.6% first afebrile, 35.8% idiopathic epilepsy, 8.1% symptomatic epileptic, and 1.5% symptomatic. 9 Our results were similar. The rate of febrile seizures was 33.6% and epilepsy 35.6%.…”
Section: Discussionsupporting
confidence: 76%
“…The rate of epilepsy among our patients with first afebrile seizures was higher compared with the rate Berksoy et al 9 and Chen et al 10 (34%) reported. In our study, 23 of 32 patients with first afebrile seizures underwent EEG, revealing epileptic activity in 11 of them.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation